2019
DOI: 10.5114/wiitm.2019.83316
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided angioplasty of dialysis fistulas in renal transplant patients.

Abstract: IntroductionPercutaneous endovascular angioplasty has become the treatment of choice for dialysis fistula stenosis. The ultrasound-guided endovascular procedure is used in patients with severe renal impairment and advanced renal transplant failure, when the need for nephrotoxic contrast administration in standard angioplasty may worsen renal function.AimTo evaluate endovascular angioplasty guided by ultrasound for dialysis fistula stenosis in renal transplant patients with severe graft insufficiency.Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the past, various procedures performed on dialysis fistulas in patients after kidney transplantation have been described. Our previous work demonstrated the possibility of percutaneous angioplasty for the successful correction of dialysis fistulas stenosis in renal transplant patients [ 15 ]. Some studies have also shown the possibility of successfully reconstructing clotted dialysis fistulas in patients returning to dialysis due to increasing transplant renal insufficiency [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, various procedures performed on dialysis fistulas in patients after kidney transplantation have been described. Our previous work demonstrated the possibility of percutaneous angioplasty for the successful correction of dialysis fistulas stenosis in renal transplant patients [ 15 ]. Some studies have also shown the possibility of successfully reconstructing clotted dialysis fistulas in patients returning to dialysis due to increasing transplant renal insufficiency [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%